PENGARUH KARAKTERISTIK AUDIT TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Barang Konsumsi Barang Primer dan Terdaftar di BEI Tahun 2019-2021) - Gian Pahala Tadore Simamora; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of audit characteristics on tax avoidance. This study has a dependent variable, namely tax avoidance with independent variables including auditor industry specialization, audit fee, audit tenure, and audit opinion. This study uses secondary data derived from the financial statements of all consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research sampling was carried out using purposive sampling method. A total of 34 companies were tested with details of 84 samples throughout the three-year research span. The analysis method used is multiple regression analysis. The results of this study indicate that audit tenure has a negative effect, while audit fee have a positive effect on tax avoidance while auditor industry specialization and audit opinion are found to have no effect.